2009
DOI: 10.1007/s11409-009-9040-x
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering students’ thinking about thinking using concept maps

Abstract: A method for uncovering students' thinking about thinking, specifically their meta-strategic knowledge, is explored within the context of an ongoing, multi-year intervention designed to promote the development of students' thinking dispositions. The development of a concept-map instrument that classroom teachers can use and an analytic framework for interpreting students' responses is presented. In a preliminary study, the concept map instrument is piloted to evaluate changes in students' conceptions of thinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 15 publications
1
32
0
13
Order By: Relevance
“…In exploring the potential reasons for pupils’ superficial metacognitive responses in the STAs investigated, it is pertinent to consider the interaction between response and pedagogy. Indeed, we found that both pupils provided relatively ‘superficial’ reflections of their own thinking and learning, a finding that parallels previous research using concept maps to explore the increasing ‘sophistication’ of pupils’ metacognitive reflections as they progress from primary to secondary school (Ritchhart et al ., ). Our finding of the relatively superficial responses provided by Primary 4 pupils in the current study is also indicative of reflections of relatively ‘surface’ rather than ‘deep’ learning, a focus on quality of learning (Biggs & Collis, ; Dart et al ., ), suggesting that this distinction can also be made in the metacognitive domain.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In exploring the potential reasons for pupils’ superficial metacognitive responses in the STAs investigated, it is pertinent to consider the interaction between response and pedagogy. Indeed, we found that both pupils provided relatively ‘superficial’ reflections of their own thinking and learning, a finding that parallels previous research using concept maps to explore the increasing ‘sophistication’ of pupils’ metacognitive reflections as they progress from primary to secondary school (Ritchhart et al ., ). Our finding of the relatively superficial responses provided by Primary 4 pupils in the current study is also indicative of reflections of relatively ‘surface’ rather than ‘deep’ learning, a focus on quality of learning (Biggs & Collis, ; Dart et al ., ), suggesting that this distinction can also be made in the metacognitive domain.…”
Section: Resultsmentioning
confidence: 97%
“…For example, classroom-based observational tools have identified indictors of metacognitive knowledge and regulation from the ages of 3 to 4 years old (Whitebread et al, 2009;Robson, 2016a,b). In addition, visual tools have been developed that elicit children's understanding of their own thinking and learning through concept maps (Ritchhart et al, 2009) and pupil views templates (PVTs; see Wall, 2008;Wall et al, 2012). In PVTs, a cartoon scenario is presented, with empty thought and speech bubbles for pupils to document their thinking in a given situation (Wall & Higgins, 2006;Wall et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the complexity of defining and measuring critical thinking, qualitative research can add additional nuances to the construct in an effort to operationalize critical thinking. Similarly, Ritchhart, Turner, and Hadar (2009) and Mathews and Lowe (2011) advocated for professional development to better understand the culture of thinking in classrooms and critical thinking dispositions. The end result involves instructors and students having overt conversations about their thinking and acknowledging when thinking is more inquisitive and active.…”
Section: Discussionmentioning
confidence: 99%
“…Concept mapping is used widely in grades K-12 to help students to organise their thoughts and represent them visually. It is also an instrument that can be used to uncover students' metacognitive thinking (Ritchhart, Turner, & Hadar, 2009). In a meta-analysis of 55 experimental and quasiexperimental studies in which students learned by constructing, modifying or viewing node-linked diagrams, Nesbit and Adesope (2006) found that the use of concept maps was associated with increased knowledge retention and this result applied across all educational levels (grades 4-8 and postsecondary), subject areas and settings.…”
Section: Personal Concept Map (Pcm)mentioning
confidence: 99%